2006
DOI: 10.1002/ajmg.b.30296
|View full text |Cite
|
Sign up to set email alerts
|

A family‐based study of Indian subjects from Kolkata reveals allelic association of the serotonin transporter intron‐2 (STin2) polymorphism and attention‐deficit‐hyperactivity disorder (ADHD)

Abstract: Serotonin transporter (SLC6A4) polymorphisms are variously implicated in mediating susceptibility to attention-deficit-hyperactivity disorder (ADHD), a highly heritable and heterogeneous disorder with onset in childhood. Since there has been no survey in this regard from India, a sample of 56 ADHD cases and 174 healthy individuals from Kolkata were genotyped for the SLC6A4 promoter (5-HTTLPR) and intron-2 (STin2) polymorphisms. We report that the observed distribution of allele frequencies is consonant with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 57 publications
(74 reference statements)
2
27
0
Order By: Relevance
“…Ten TDT (Banerjee et al 2006;Heiser et al 2007;Kent et al 2002;Kim et al 2005a;Li et al 2007;Waldman et al unpublished data;Wigg et al 2006;Xu et al 2008Xu et al , 2005b and nine Case-Control/HHRR (Beitchman et al 2003;Curran et al 2005;Guimares et al 2007;Kopeckova et al 2008;Langley et al 2003;Manor et al 2001;Seeger et al 2001;Zhao et al 2005;Zoroglu et al 2002) studies were identiWed for the present meta-analysis of the association between childhood ADHD and the 5HTTLPR with the long variant designated as the "risk" allele. Results of this metaanalysis, shown in Fig.…”
Section: Serotonin Transporter Gene (Slc6a4; 5htt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ten TDT (Banerjee et al 2006;Heiser et al 2007;Kent et al 2002;Kim et al 2005a;Li et al 2007;Waldman et al unpublished data;Wigg et al 2006;Xu et al 2008Xu et al , 2005b and nine Case-Control/HHRR (Beitchman et al 2003;Curran et al 2005;Guimares et al 2007;Kopeckova et al 2008;Langley et al 2003;Manor et al 2001;Seeger et al 2001;Zhao et al 2005;Zoroglu et al 2002) studies were identiWed for the present meta-analysis of the association between childhood ADHD and the 5HTTLPR with the long variant designated as the "risk" allele. Results of this metaanalysis, shown in Fig.…”
Section: Serotonin Transporter Gene (Slc6a4; 5htt)mentioning
confidence: 99%
“…For the meta-analysis of association between childhood ADHD and the 5HTT STin2 polymorphism, two TDT (Li et al 2007;Xu et al 2008) and seven Case-Control/HHRR (Banerjee et al 2006;Heiser et al 2007;Kim et al 2005a;Langley et al 2003;Xu et al 2005b;Zoroglu et al 2002) studies were identiWed. Based on an initial study reporting reduced prevalence of the 12-repeat allele among children diagnosed with ADHD (Zoroglu et al 2002), the 10-repeat allele of the STin2 polymorphism was designated as the "risk" allele.…”
Section: Serotonin Transporter Gene (Slc6a4; 5htt)mentioning
confidence: 99%
“…These genes have been reported to have paternal or maternal transmission or parent-of-origin effects in ADHD in previous studies. [6][7][8][9][10][11][12][13][14][15] In the cleaned SNP data, we did not find any SNPs in the DRD4 gene. Furthermore, we could not confirm the paternal or maternal transmission or parent-oforigin effects (p < 0.01) for HTR1B, SLC6A4, DRD4, DRD5 and FADS2.…”
Section: Discussionmentioning
confidence: 73%
“…In accord with these data two other studies found that short/short genotype was significantly underrepresented in children with ADHD compared to controls [Manor et al, 2001;Zorog lu et al, 2002]. However, Li et al [2007] reported a preferential transmission of the short-allele to ADHD offspring in a Chinese sample and six further studies did not find any association between the polymorphism and ADHD [Langley et al, 2003;Kim et al, 2005;Xu et al, 2005;Banerjee et al, 2006;Wigg et al, 2006;Heiser et al, 2007]. A study that combined the available data by pooling odds ratios across studies found a small but significant association of the long allele of 5-HTTLPR with ADHD [Faraone et al, 2005].…”
mentioning
confidence: 69%
“…For the STin2-VNTR marker one study found that the 12/12 genotype was significantly less frequent in ADHD cases compared to controls [Zorog lu et al, 2002], while another study found that the 12-repeat allele was preferentially overtransmitted to ADHD offspring [Banerjee et al, 2006]. A further seven studies did not demonstrate an association between STin2-VNTR and ADHD [Kent et al, 2002;Langley et al, 2003;Curran et al, 2005;Kim et al, 2005;Xu et al, 2005;Heiser et al, 2007;Li et al, 2007].…”
mentioning
confidence: 99%